(untitled) (Communications in Mathematical Research, 2021)
This paper concerns the Cauchy problem for compressible Navier-Stokes equations. The weak dissipative structure is explored and a new proof for the classical solutions are shown to exist globally in time if the initial data is sufficiently small.